A Comparison of the Impact of Differences in New Media Content on the Self-Efficacy of Female Adolescents - Hao, Zitong (Pinnacle Academic Press Proceedings Series, 2026)
This study investigates the mechanisms through which differences in new media content influence the self-efficacy of female adolescents. Drawing on contemporary theories of media effects and adolescent psychological development, the paper distinguishes between positive-oriented and negative-oriented new media content and examines their respective impacts across multiple domains of self-efficacy. Positive-oriented content, including knowledge popularization, inspirational narratives, and materials that foster social and communication skills, is found to enhance academic confidence, interpersonal competence, self-cognition, emotional regulation, life skills, and problem-solving abilities. In contrast, negative-oriented content, such as excessive entertainment consumption, appearance-focused and comparison-driven materials, and misleading or falsely curated social media displays, is associated with diminished self-efficacy in these same domains. The analysis highlights a notable symmetry and pertinence between the type of content consumed and the specific dimension of self-efficacy affected, suggesting a patterned and domain-sensitive relationship rather than a uniform global effect. These findings underscore the pivotal role of new media environments in shaping the psychological development and adaptive functioning of female adolescents. The study further provides an academic perspective for understanding the correlation mechanisms linking media content characteristics with self-beliefs, and it offers implications for educators, parents, and policymakers seeking to guide healthier media use and design targeted interventions to support adolescent well-being.